Monoparesis. Complication of constant positive airways pressure. Issue 2 (February 1975) - Turner, T; Evans, J; Brown, J K
Abstract : Erb's palsy has been observed in 2 infants who had been treated with constant positive airways pressure for idiopathic respiratory distress syndrome. Both infants made complete neurological recovery from what was thought to be an acquired injury from the neck seal.